Lipolytic Enzymes with Hydrolytic and Esterification Activities Produced by Filamentous Fungi Isolated from Decomposition Leaves in an Aquatic Environment. (2nd June 2019) - Mendes, D. B.; Silva, F. F. Da; Guarda, P. M.; Almeida, A. F.; Oliveira, D. P. de; Morais, P. B.; Guarda, E. A.
Abstract : Microbial lipases are prominent biocatalysts able to catalyze a wide variety of reactions in aqueous and nonaqueous media. In this work, filamentous fungi isolated from leaves decomposed in an aquatic environment were screened for lipase production with hydrolytic activity and esterification. Agar plates with Tween 20 and Rhodamine B were used for selection, while submerged cultures with olive oil were subsequently used to select 38 filamentous fungi. Trichoderma harzianum, Fusarium solani, Trichoderma harzianum F5, and Penicillium sp. F36 were grown in six different culture media. F. solani presented the highest lipase production (2.37 U/mL) with esterification activity of 0.07 U/mL using medium composed of (g.L −1 ) KH2 PO4 1.00, MgSO4 H2 O 1.123, and CuSO4 0.06. Supplementation of this culture medium with organic nitrogen sources increased lipase production by 461.3% using tryptone and by 419.4% using yeast extract. Among the vegetable oils from the Amazon region, degummed cotton oil induced lipase production up to 8.14 U/mL. The lipase produced by F. solani F61 has great potential to application in conventional processes and biodiesel production by transesterification of vegetable oils, as well as food industries in the production of fatty acid esters by hydrolysis and esterification.